Konseptualisasi Qat'i dan Zanni dalam Diskursus Usul Fikih - Syufa'at Syufa'at (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2009)
Qat'iy and zanni consist of two elements; al-thubut (the truth of the source) and al-dalalah (meaning). There are no differences in arguments about the truth of the Al-Qur'an source. The problems are in the contents since it depends on the intellectual capacity of mufassir.